PENGARUH BEBAN KERJA DAN KESEIMBANGAN KEHIDUPAN - KERJA TERHADAP KEPUASAN KERJA - Dwi Rekta Ramadhan (Jurnal Ekonomi dan Bisnis, 2024)
Network companies such as PT Nexwave are companies that operate in network management in collaboration with network provider companies. To realize its clients' requests, PT Nexwave must of course always strive to maximize existing resources. However, are there internal problems that can hinder or influence human resources in realizing company goals? In this research, factors emerged that were predicted to have an influence on employee job satisfaction, namely workload and work-life balance. The aim of this research is to examine workload, work-life balance and job satisfaction and determine the influence of workload and work-life balance on job satisfaction of employees of PT Nexwave Bandung City branch. The research method used is a descriptive and verification method using path analysis and the t- test difference test for partial testing and the F-test difference test for simultaneous testing. The data collection technique used a questionnaire distributed to 121 employee respondents at PT Nexwave Bandung City branch. The results of this study showed that the workload was in the high category, work-life balance was in the fairly high/medium category, and job satisfaction was in the moderate category. high/medium. The results of the path analysis show that workload has a significant negative influence on job satisfaction, while work-life balance has a significant positive influence on job satisfaction.